MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA CEMPLANG MELALUI PENGEMBANGAN MARKETING UMKM SNACK RENGGINANG - Fidziah, Fidziah; Lesmana, Ihwan Satria (Jurnal Abdimas Bina Bangsa, 2025)
Community service activities carried out in Cemplang Village aim to improve community welfare through empowering MSMEs, especially in developing marketing of rengginang products. This activity includes training in digital marketing skills, use of social media and marketplace platforms to expand market reach. Branding training is provided to help MSMEs create a strong product identity, which increases product attractiveness and competitiveness. The results obtained show that MSMEs have succeeded in improving their marketing capabilities, with rengginang products that can now be reached by a wider range of consumers, both at the local level and through digital platforms. However, challenges such as difficulties in managing digital technology and limited understanding of more complex digital marketing strategies still need to be overcome. Therefore, ongoing assistance is needed to ensure the sustainability and development of their businesses in an increasingly competitive market